2010
DOI: 10.1111/j.1365-2702.2010.03271.x
|View full text |Cite
|
Sign up to set email alerts
|

Managing pain in children: where to from here?

Abstract: Despite the evidence to guide practice being readily available children continue to experience unrelieved pain. The strategies identified in this article may help to ensure that pain is relieved effectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
1
5

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(50 citation statements)
references
References 59 publications
2
42
1
5
Order By: Relevance
“…Research exploring the attitudes of health professionals regarding pediatric pain management is plentiful and presents a general consensus: Health professionals' values and beliefs influence the treatment of children's pain (Melhuish & Payne, 2006;Twycross, 2010;Young, 2005). The literature shows that current values still run the risk of being influenced by the historical myths highlighted at the beginning of this discussion.…”
Section: Practitioner Values and Beliefsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research exploring the attitudes of health professionals regarding pediatric pain management is plentiful and presents a general consensus: Health professionals' values and beliefs influence the treatment of children's pain (Melhuish & Payne, 2006;Twycross, 2010;Young, 2005). The literature shows that current values still run the risk of being influenced by the historical myths highlighted at the beginning of this discussion.…”
Section: Practitioner Values and Beliefsmentioning
confidence: 99%
“…Although research has demonstrated the safety of various analgesics and guidelines abound (Krauss, 2001), the literature demonstrates a gap in front-line staff consistently applying this knowledge to current practice (Czarnecki et al, 2011;Twycross, 2010). Twycross (2010) linked this gap to the possibility that staff do not necessarily understand the rationale behind pain relieving strategies. Studies have demonstrated that some nursing staff determined a doctor's order of "PRN" or pro re nata pain relief to mean "as little as possible", rather than "when necessary" (Kortesluoma & Nikkonen, 2004).…”
Section: Practitioner Values and Beliefsmentioning
confidence: 99%
“…Evidence from this study suggested that student nurses' lacked knowledge and confidence in relation to physiology, pharmacology of pain, child development and cultural practices which may need to be revisited throughout the undergraduate nursing programme. However, structured pain management programmes can be of benefit in the development of student nurses' attitudes towards the management of pain in children and could potentially impact on future pain management practices (Twycross (2010).…”
Section: Discussionmentioning
confidence: 99%
“…Fagkunnskaper og gode holdninger er avgjørende for å lindre smerte. Til tross for at det de siste årene er publisert mye om barn og smerte (12), rapporteres sykepleieres holdninger og manglende kunnskaper som viktige årsaker til utilfredsstillende smertelindring (13). Frykt for overmedisinering, frykt for tilvenning til opioider og engstelse for respirasjonsdepresjon, er noen av områdene det eksisterer mangelfulle kunnskaper innenfor (8,(14)(15)(16)(17).…”
Section: Introduksjonunclassified